Bioenergetics and biomechanics of cycling: the role of `internal work` - Minetti, A. E. (European Journal of Applied Physiology, 2011)
The `dissection` of energy expenditure of cycling into the metabolic equivalent of the different forms of mechanical work done, inaugurated 30 years ago by di Prampero and collaborators, has been much debated in the last few decades. The mechanical internal work, particularly, which is currently associated to the movement of the lower limbs, has been approached, estimated and discussed in several different ways and there is no agreed consensus on its role in cycling. This paper, through re-processing previously published data of oxygen consumption during pedalling at different frequency, external load and limb mass, proposes a model equation and a multiple non-linear regression as the method to assess the internal work of cycling. With that tool a very consistent metabolic equivalent of the internal work is obtained. However, a software simulation of pedalling limbs showed, as suggested in the literature, that the link with the chain ring allows the system to passively revolve forever, after an initial push. This result challenges the very existence of the `kinematic internal work` of cycling. We conclude and suggest that the `viscous internal work`, an often neglected and almost unmeasurable portion of the internal work that could be proportional to the `kinematic` form, is responsible for the extra metabolic expenditure as measured when the pedalling frequency of cycling increases.